Relationship Between Compressive Strength and Tensile Strength in High-Strength Concrete - علي محمود إغليو; إمحمد حسن القط; عبد الكريم خليفة الأطرش; Shafter عبد الله علي (Journal of Pure & Applied Sciences, 2024)
In this study, laboratory tests were conducted on concrete specimens to determine the compressive strength and tensile strength of high-strength concrete. The compressive strength was calculated by testing 12 (10 cm x 10 cm x 10 cm) cubes for each of three workability (low, medium, and high). The tensile strength was calculated using a direct shear test by testing 8 (15 cm x 15 cm) cylinders for each workability. The relationships between compressive strength and tensile strength of high-strength concrete were then determined for each workability. The results indicated that compressive strength increased with a decrease in the water-to-cement ratio (W/C) for all workabilities. The results also indicated that tensile strength increased with a decrease in W/C, but for the low workability, tensile strength decreased with a decrease in W/C until W/C = 0.45, after which tensile strength began to increase. The results also indicated that tensile strength ranged from 6% to 8% of compressive strength for all workabilities. Finally, the results indicated that the coefficient of variation (C.V) of tensile strength, compressive strength, and the tensile-to-compressive strength ratio decreased with increasing workability. This means that the results were more consistent with increasing mix. On the other hand, W/C ratio was more consistent with decreasing workability.